Self- Access Materials Needed for Autonomous Learning in the 21st Century at Senior High School - Diah Nur Afdillah; Farouk Imam Arrasyid (International Journal of Education and Humanities, 2021)
The existence of the covid- 19 pandemic can indeed be a polemic in all sectors, particularly in education sector. Besides the covid- 19 pandemic, the rapid progress of the 21st encourages students to become independent learners who can pursue their own studying. Self- access materials play a crucial role in the successful execution of autonomous learning goals in promoting the ability and passion of students for autonomous learning. Therefore, this research aims to find out self- access materials needed for autonomous learning in the 21st century and investigate how to implement the self- access materials for autonomous learning in the 21st century. This research is a descriptive qualitative research using interview to collect the data. The respondents of this research are 6 students of XI Grade and 1 English teacher. The result shows there are 6 strategies of autonomous learning which consist of 17 autonomous learning activities. From the 17 autonomous learning activities, there are 13 autonomous learning strategies that found in this research with 1 activities founded regarding to the interviewees responses. The self- access materials needed by students are didactic books, motivational videos, dictionary applications, YouTube, vocabulary books, registers, authentic materials, English textbooks according to curriculum, webtoons, novels, feedback worksheet, TOEFL CD-Room, educational software (British Council, BBC Learning English and social media, articles, Ome TV application and others. There are 7 steps to implement the self- access materials. Thus, to support the English learning, this research greatly beneficial for students, teachers and material developers